2023
DOI: 10.1038/s41598-023-45508-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid with all-cause and cardiovascular mortality in obstructive sleep apnea

Zhe Yang,
Tian Lv,
Xiaoheng Lv
et al.

Abstract: The study investigated the association between Serum Uric Acid (SUA) levels and all-cause as well as cardiovascular mortality in patients with Obstructive Sleep Apnea (OSA). This prospective cohort study enrolled participants with OSA from four cycles of the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2008, and 2015–2018. A weighted Cox proportional hazards model was used to assess adjusted hazard ratios (aHRs) and their corresponding 95% confidence intervals (CI) for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…One meta-analysis also reported that individuals with OSA had higher serum uric acid levels compared to the control group [27]. Moreover, serum uric acid was associated with all-cause mortality and cardiovascular mortality in individuals with OSA which was determined using the NHANES screening questionnaire [28]. A bidirectional two-sample Mendelian randomization study was conducted using data from publicly available genome-wide association study summary statistics [29].…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis also reported that individuals with OSA had higher serum uric acid levels compared to the control group [27]. Moreover, serum uric acid was associated with all-cause mortality and cardiovascular mortality in individuals with OSA which was determined using the NHANES screening questionnaire [28]. A bidirectional two-sample Mendelian randomization study was conducted using data from publicly available genome-wide association study summary statistics [29].…”
Section: Discussionmentioning
confidence: 99%